Endometrial hyperplasia: current approaches to diagnosis and treatment. Literature review and own experience - T.F. Tatarchuk; Y.O. Dubossarska; Z.M. Dubossarska; S.I. Regeda; O.V. Zanko (Publishing House TRILIST, 2021)
Purpose of the study: to examine the morphological and immunohistochemical features of the endometrium in postmenopausal women with uterine bleeding, depending on body weight and metabolic syndrome. Materials and methods. The study included 114 women with postmenopausal uterine bleeding. Women were divided into 3 groups. Group I included 41 patients with overweight and obesity class I-II, group II - 43 women with metabolic syndrome, group III (control) consisted of 30 patients with normal body weight. Hysteroscopy with morphological analysis of biopsied material was performed for all patients of groups I and III and 41 patients of group II. Pathohistological and immunohistochemical analysis were used to diagnose endometrial pathology. The level of cell proliferation in the endometrium was assessed by immunohistochemical analysis using monoclonal antibodies for Ki-67 expression; antiapoptotic activity was determined by the Bcl-2 and COX-2 expression. Results. Endometrial pathology was diagnosed in 94.74% of women. Endometrial polyps in the structure of the identified pathologyprevailed in group I and control group III (82.93% and 83.33%, respectively), while endometrial polyps were detected in 25.59% of women in the group II. Endometrial hyperplasia was diagnosed in the vast majority (69.76%) in group II, hyperplasia without atypia was detected in 51.16% and endometrial hyperplasia with atypia in 18.60%. Conclusions. Endometrial hyperplasia value was higher in postmenopausal women with metabolic syndrome compared to patients with normal weight, overweight and obesity. There was an increase of Ki-67, Bcl-2 and COX-2 expression in the endometrial glands in women with metabolic syndrome in comparison to patients with normal weight and obesity, for which only increased Bcl-2 expression in the stroma was observed. This confirms the existing data on the predominance of the apoptosis inhibition over proliferation in the formation of endometrial diseases in the postmenopausal period and confirms the combination of hyperproliferative processes and apoptosis inhibition if there is metabolic syndrome.